Nilai Prediktif Distorsi QRS pada Infark Miokard Akut Anterior - Budhi Setianto; Nur Haryono (The Indonesian Heart Association, 2007)
Background. The initial ECG at patients with Acute Coronary Syndrome, especially STEMI can predict size of infarction, response to reperfusion therapy and long term prognosis. A new classification, the QRS distortion have increased mortality rates and larger infarct size and less limitation of their infarct size by thrombolytic therapy. QRS distortion is the emergence of J point = 50% of R wave in leads with qR configuration (I, aVL, V4-V6), or disappearance of the S wave in leads with Rs configuration (V1-V3). Methods and results.This study is cohort-retrospective to patients with anterior IMA treated by thrombolytic at National Cardiovascular Centre – Harapan Kita, Jakarta, Indonesia, during January 2003 – September 2004, that fulfill inclusion and exclusion criterias. They were divided into two group, with QRS distortion (+) and without QRS distortion (-); each group consist of 30 patients. Correlation between the two groups were ana-lyzed by t test, chi-square test, Mann Whitney u test and logistic regres-sion. Patients age range is 40 – 69 years, and mostly man. There is no difference between baseline characteristic in the two groups, except cho-lesterol LDL which is higher in the group with QRS distortion. Patients with QRS distortion have a higher tendency of thrombolytic therapy fail-ure compare to patients without QRS distortion, (p=0,003). As the con-sequence they also have a higher rate of arrhythmia events, low ejection fraction and re-hospitalization due to congestive heart failure.Conclusions. The prognosis of patients with anterior IMA associated with QRS distortion is worse than without QRS distortion.